Early ceramic trade in Gansu and Qinghai regions, northwest China: A comparative elemental analysis on sherds of Majiayao culture, Yangshao culture and Qijia culture. (September 2015) - Cui, Yifu; Dong, Guanghui; Li, Haiming; An, Ting; Liu, Xinyi; Wang, Jian; Wang, Hui; Ren, Xiaoyan; Li, Xiaobin; Chen, Fahu
Abstract: This article explores the possibility of early ceramic exchange in Gansu and Qinghai regions in late prehistory. X-ray fluorescence (XRF) measurement, principal component analysis (PCA) and cluster analysis are conducted on 118 potsherds that date to the late Yangshao culture (5500–4900 a BP), early Majiayao culture (5300–4800 a BP) and Qijia culture (4400–3600 a BP). The fragments were gathered from 66 archeological sites in Gansu and Qinghai regions, northwest China. The composition of Red Clay and loess from Gansu and Qinghai provinces is examined and compared with that of pottery clay. Our result shows that during the late Yangshao and early Majiayao periods, most potsherds were made from local clay which contains distinct regional elemental signals. During the Qijia period, on the other hand, there is little difference in the elemental composition of pots found in different regions. Those results suggest that during the Qijia period, communities living in Gansu and Qinghai exchanged ceramics or clay to make those pieces.